2012
DOI: 10.1038/nnano.2011.251
|View full text |Cite
|
Sign up to set email alerts
|

Transport spectroscopy of symmetry-broken insulating states in bilayer graphene

Abstract: Bilayer graphene is an attractive platform for studying new two-dimensional electron physics, because its flat energy bands are sensitive to out-of-plane electric fields and these bands magnify electron-electron interaction effects. Theory predicts a variety of interesting broken symmetry states when the electron density is at the carrier neutrality point, and some of these states are characterized by spontaneous mass gaps, which lead to insulating behaviour. These proposed gaps are analogous to the masses gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

68
459
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(531 citation statements)
references
References 41 publications
(21 reference statements)
68
459
4
Order By: Relevance
“…Bilayer graphene Bilayer graphene has received a lot of attention, mainly because of the enhanced density of states at zero doping due to parabolically touching bands. Such band structures have been shown to be unstable towards spontaneous symmetry breaking [152] and experimental results have revealed signatures of interaction-driven excitonic states in suspended and undoped graphene bilayers [18,19,20,21,22,23,24,25]. Very recently weak-coupling renormalization group calculations have shown that superconductivity emerges upon doping away from these excitonic states [153].…”
Section: Graphene-like Systemsmentioning
confidence: 99%
“…Bilayer graphene Bilayer graphene has received a lot of attention, mainly because of the enhanced density of states at zero doping due to parabolically touching bands. Such band structures have been shown to be unstable towards spontaneous symmetry breaking [152] and experimental results have revealed signatures of interaction-driven excitonic states in suspended and undoped graphene bilayers [18,19,20,21,22,23,24,25]. Very recently weak-coupling renormalization group calculations have shown that superconductivity emerges upon doping away from these excitonic states [153].…”
Section: Graphene-like Systemsmentioning
confidence: 99%
“…2,3 Recent advances in obtaining suspended bilayer graphene devices with charge carrier mobility exceeding μ > 10 000 cm 2 V −1 s −1 gave access to the investigation of many-body phenomena in clean bilayer graphene at low charge carrier concentration (n < 10 10 cm −2 ). [4][5][6][7][8][9][10][11] Due to the nonvanishing density of states at the charge neutrality point (CNP), bilayer graphene is predicted to have a variety of ground states triggered by electron-electron interaction. There are two competing theories describing the ground state of BLG: a transition (i) to a gapped layer-polarized state [12][13][14][15][16][17] (excitonic instability) or (ii) to a gapless nematic phase.…”
Section: Introductionmentioning
confidence: 99%
“…12,16,17 Recent experiments have suggested evidence of the possible existence of two of the antiferromagnetic states-the anomalous quantum Hall (AQH) state 5,6 and the spin-polarized layer-antiferromagnetic (LAF) state. 7 To avoid possible confusion we note that in earlier literature 16 the LAF state is also called the quantum valley Hall state. The AQH state has electrons that are polarized in the same layer for both spins and in opposite layers for opposite valleys.…”
Section: Introductionmentioning
confidence: 99%
“…One promising approach is to apply the gate electric field perpendicular to the AB (Bernal) stacked bilayer graphene (BLG) to break the inversion symmetry of sublattices 6,7,[9][10][11] . Such an induced band gap of GBLG can be tuned in a wide range by field strength 9,[11][12][13] , offering an important degree of freedom to optimize performance of graphene devices.…”
mentioning
confidence: 99%
“…For instance, electrical conductance experiments [11][12][13] have confirmed the existence of a finite QP band gap but their measured value is disturbed by many extrinsic factors, e.g., the inevitable contact resistance between the electrodes and graphene sheet. While noncontacting optical measurements [8][9][10] have revealed a tunable band gap in GBLG, these results are indirect because the optical absorption peak (edge) is not conceptually equivalent to the QP band gap 14,15 .…”
mentioning
confidence: 99%